The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.brainres.2012.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Getting real about Semantic Illusions: Rethinking the functional role of the P600 in language comprehension

Abstract: In traditional theories of language comprehension, syntactic and semantic processing are inextricably linked. This assumption has been challenged by the 'Semantic Illusion Effect' found in studies using Event Related brain Potentials. Semantically anomalous sentences did not produce the expected increase in N400 amplitude but rather one in P600 amplitude. To explain these findings, complex models have been devised in which an independent semantic processing stream can arrive at a sentence interpretation that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
450
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(517 citation statements)
references
References 121 publications
35
450
1
4
Order By: Relevance
“…For example, Deacon and colleagues [10] and Kiefer [11] observed N400 priming effects with very short SOAs (< 70 ms) in a masked priming paradigm, suggesting that the underlying mechanism must have been ASA. Similarly, Brouwer and colleagues [12] suggest that the N400 is exclusively linked to lexical retrieval, while (post-lexical) semantic integration is supposed to be reflected by the P600 component. Moreover, as neuroimaging studies found consistent priming effects for the brain structure assumed to house the lexical semantic network (e.g., the posterior part of the middle temporal gyrus, pMTG), the influential review paper by Lau and colleagues [13] argued that retrievalrelated processes including ASA are likely to always contribute to N400 priming effects, irrespective of SOA duration.…”
Section: Priming Effects On the N400mentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Deacon and colleagues [10] and Kiefer [11] observed N400 priming effects with very short SOAs (< 70 ms) in a masked priming paradigm, suggesting that the underlying mechanism must have been ASA. Similarly, Brouwer and colleagues [12] suggest that the N400 is exclusively linked to lexical retrieval, while (post-lexical) semantic integration is supposed to be reflected by the P600 component. Moreover, as neuroimaging studies found consistent priming effects for the brain structure assumed to house the lexical semantic network (e.g., the posterior part of the middle temporal gyrus, pMTG), the influential review paper by Lau and colleagues [13] argued that retrievalrelated processes including ASA are likely to always contribute to N400 priming effects, irrespective of SOA duration.…”
Section: Priming Effects On the N400mentioning
confidence: 91%
“…Various recent articles (Lau et al, 2008;Brouwer et al, 2012) have revived the idea that only processes during word-retrieval (such as automatic spreading activation, ASA) are strongly supported, while post-lexical integrative processes are not. The present ERP study replicates a behavioral study by McKoon and Ratcliff (1995) who demonstrated that a prime-target pair such as finger -hand shows stronger priming when a majority of other pairs in the list share the analogous semantic relationship (here: part-whole), even at short stimulus onset asynchronies (250 ms).…”
mentioning
confidence: 99%
“…(2012) argued for a functional reinterpretation of the ERP components involved. First of all, in line with previous suggestions (Kutas & Federmeier, 2000; Lau, Phillips, & Poeppel, 2008; van Berkum, 2009), they propose that the N400 component reflects retrieval of lexical‐semantic information, rather than semantic integration or any other kind of compositional semantic processing.…”
Section: The Retrieval–integration Accountmentioning
confidence: 99%
“…First, some researchers adopted the integration view of the N400 (e.g., Hagoort et al, 2004) and have taken these results to indicate that comprehenders fail to detect implausibility in role-reversed sentences at least initially 3 ("Semantic Illusion" hypothesis, e.g., Bornkessel-Schlesewsky & Schlesewsky, 2008;Hoeks et al, 2004;Kim & Osterhout, 2005;Kolk et al, 2003;Kuperberg, 2007 On the other hand, some have focused on the N400's sensitivity to lexical semantic association and have attributed the lack of an N400 effect to argument role reversals to the fact that the verb tends to be strongly associated with its arguments in both canonical and rolereversal sentences (Brouwer, Fitz, & Hoeks, 2012). Under this view, argument role reversals should fail to modulate the N400 only when the verb is strongly associated with the arguments, and they should elicit an N400 effect when the verb is only weakly associated with the arguments.…”
Section: Prediction In the Processing Of Thematic Relationsmentioning
confidence: 99%